2022
DOI: 10.3389/fsurg.2022.922595
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of systemic immune-inflammation index in surgical esophageal cancer patients: An updated meta-analysis

Abstract: PurposeTo identify the prognostic role of systemic immune-inflammation index (SII) in esophageal cancer patients receiving operation.MethodsThe PubMed, EMBASE, Web of Science, Cochrane Library, WanFang and CNKI electronic databases were searched up to February 17, 2022 for relevant studies. The hazard ratios (HRs) and 95% confidence intervals (CIs) were combined to assess the association between SII and prognosis in surgical esophageal cancer patients. The primary outcome was overall survival (OS) and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Actually, the clinical role of pretreatment SII in esophageal cancer has been manifested by several meta-analysis. [21,39,40] Zhang et al included 5 relevant studies involving 2292 cases and revealed that increased SII was associated with shorter OS in esophageal cancer patients after surgery (HR = 1.34, 95% CI: 1.15–1.53, P < .001). [40] Li et al included 9 retrospective studies involving 3565 participants and their results showed that high SII was related to poor OS (HR = 1.58, 95% CI: 1.23–2.02, P < .001) in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the clinical role of pretreatment SII in esophageal cancer has been manifested by several meta-analysis. [21,39,40] Zhang et al included 5 relevant studies involving 2292 cases and revealed that increased SII was associated with shorter OS in esophageal cancer patients after surgery (HR = 1.34, 95% CI: 1.15–1.53, P < .001). [40] Li et al included 9 retrospective studies involving 3565 participants and their results showed that high SII was related to poor OS (HR = 1.58, 95% CI: 1.23–2.02, P < .001) in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Li et al included 9 retrospective studies involving 3565 participants and their results showed that high SII was related to poor OS (HR = 1.58, 95% CI: 1.23–2.02, P < .001) in esophageal cancer. However, their subgroup analysis indicated that elevated preoperative SII was only related to poor OS (HR = 1.72, 95% CI: 1.34–2.21, P < .001), PFS (HR = 1.94, 95% CI: 1.61–2.35, P < .001) and cancer-specific survival (CSS) (HR = 1.44, 95% CI: 1.04–1.99, P = .027) of ESCC patients, [21] which is consistent with the findings in the meta-analysis by Yang et al [39] Radiation could cause a certain amount of inflammation in the body and patients with high basic levels of inflammatory response are suggested to experience more serious side effects of radiotherapy. Thus, ESCC patients with increased pre-radiotherapy SII are more likely to have poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to previously published study, variables were calculated by the following formula: aggregate index of systemic inflammation (AISI) = MONO × PLT× NEUT/LY, 26 SII = PLT × NEUT/LY. 27 …”
Section: Methodsmentioning
confidence: 99%
“…There have been many studies investigating the effects of systemic inflammatory responses such as neutrophil/lymphocyte ratio (NLR), platelet/ lymphocyte ratio (PLR) and monocyte/lymphocyte ratio (MLR) on prognosis. [3] Systemic immune-inflammation index (SII) is an inflammatory response marker calculated based on absolute platelet, neutrophil, and lymphocyte counts. It shows the patient's systemic immune stimulation level and immune response level.…”
Section: Introductionmentioning
confidence: 99%